THE EFFECTS OF ERROR TREATMENT ON INTERLANGUAGE: A CASE STUDY OF INDONESIAN LEARNERS LEARNING ENGLISH AS A FOREIGN LANGUAGE - Endang Fauziati (Universitas Muhammadiyah Surakarta, 2010)
This study investigates the effects of a short-term error treatment (ET) on ILerrors, with specific attention to the learners’ ungrammatical items. The problemstates “what are the effects of a ET on the learners’ ungrammatical items?”, Aretheir ungrammatical items fossilized (in a sense that they are static in nature) ordynamic after the learners have been exposed to the ET. The data were the learners’ free compositions collected four times: prior and after the ET and two months afterwards. They were analyzed quantitatively and qualitatively. The result indicates that the ET changed the state of the learners’ ungrammatical items. Theybecame so dynamic. At a certain period, some appeared; then due to the ET, some were destabilized, some were fluctuating, and others were still stabilized. New errors appeared as they started learning to use new grammatical items. The conclusion drawn from this study is that ET can change the state of the learners’ ILerrors; ET contributes to the destabilization process. Errors may persist momentarily but they can be destabilized. The ET still works on the learners who are at their post puberty. Thus, there is a great possibility for the learners to acquire complete TL grammar since their ungrammatical items are dynamic.Key words: error treatment, interlanguage, fossilized, stabilization.